Review of Local Scientific Research Work on Saw Fiber Separation - Khusanova Shahida Alibek's Qizi; Lalijonov U; Isoqov S; Muxtorova M (Genius Publishing Group, 2022)
Local research work on the efficiency of the processing of the separation of sawdust fiber and the removal of cotton fiber from the sawdust teeth has been studied.
Keywords: Cotton; gin; technique; product